2019
DOI: 10.1002/ctpp.201900038
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely propagating quantum solitary waves in quantum‐magnetized plasma with ultra‐relativistic degenerate electrons and positrons

Abstract: The oblique propagation of the quantum electrostatic solitary waves in magnetized relativistic quantum plasma is investigated using the quantum hydrodynamic equations. The plasma consists of dynamic relativistic degenerate electrons and positrons and a weakly relativistic ion beam. The Zakharov‐Kuznetsov equation is derived using the standard reductive perturbation technique that admits an obliquely propagating soliton solution. It is found that two types of quantum acoustic modes, that is, a slow acoustic mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Putting Equations (12)- (14) into the basic Equations (6)-(8) and collecting the terms of different powers of ε, the non-zero order of ε leads to the following expressions:…”
Section: Non-linear Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Putting Equations (12)- (14) into the basic Equations (6)-(8) and collecting the terms of different powers of ε, the non-zero order of ε leads to the following expressions:…”
Section: Non-linear Analysismentioning
confidence: 99%
“…First, most previous studies have considered that degenerate particles, such as electrons and positrons, are completely degenerate and cold (i.e., T e,p = 0), where e and p for the electron and for the positron, respectively. [5,[7][8][9][10][11][12][13][14] Second, it was less commonly assumed that degenerate particles are at non-zero temperature T e,p ≠ 0. [15][16][17][18][19][20][21][22][23] It is the last method that interests us here even though most authors also mention a zero-temperature approach to simplify the mathematical treatment in their plasma models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From analysis, it was seen that only positive potential cnoidal waves are produced. The quantum hydrodynamic equations were used to examine the oblique propagation of quantum electrostatic solitary waves in a magnetized relativistic quantum plasma [19] by deriving the ZK equation. It was found that two types of quantum acoustic modes, a slow acoustic mode and a rapid acoustic mode, may propagate.…”
Section: Introductionmentioning
confidence: 99%